Consumo de alimentos en niños menores de 5 años en comunidades rurales de Costa Rica, 1977 - Brenes, Haydeé; Mata, Leonardo (Revista de Biología Tropical, 1978)
Six Costa Rican communities of different ecological,-" settings were selected for the study of road intake in children under 5 years of age. Intake was expressed as calorie and protein adequacy. Calorie defficiency was more prevalent than protein defficiency. Practically there were no differences in adequacy by age, although 4 year-olds had a slightly greater defficiency than younger children. Calorie and protein intake was lower in this study than observed in a. relatively more advanced rural region 4 years earlier. Only 13 per cent of the children selected at random were covered by Social Development and Family Allowances programs which provide for two "hot meals" per day. Calorie defficiencies of children benefiting from this program were of similar magnitude as those of children not attending the food distribution centers. These observations point to the need to carry out further investigation of the actual effectiveness and drawbacks of such programs.